2009
DOI: 10.1038/nprot.2009.201
|View full text |Cite
|
Sign up to set email alerts
|

EOS lentiviral vector selection system for human induced pluripotent stem cells

Abstract: Generation of induced pluripotent stem (iPS) cells from patients has exciting applications for studying molecular mechanisms of diseases, screening drugs and ultimately for use in cell therapies. However, the low efficiency and heterogeneous nature of reprogramming is a major impediment to the generation of personalized iPS cell lines. We reported in Nature Methods (6, 370-376, 2009) the first selection system to enrich for reprogrammed human iPS cells. Using a lentiviral vector that specifically expresses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 37 publications
0
84
0
Order By: Relevance
“…Using the strong LTR promoter from ETn and Oct4 and/or Sox2 binding motifs, the EOS viral vector reporters robustly mark iPS cells with EGFP during reprogramming by overcoming vector silencing (Hotta et al, 2009a;Hotta et al, 2009b). We used EOS-S(4+)-EmGFP reporter (Hotta et al, 2009b) manufactured as BacMam viruses ( Fig.…”
Section: Fully Reprogrammed Ips Cell Lines Generated By the Bacmam Trmentioning
confidence: 99%
“…Using the strong LTR promoter from ETn and Oct4 and/or Sox2 binding motifs, the EOS viral vector reporters robustly mark iPS cells with EGFP during reprogramming by overcoming vector silencing (Hotta et al, 2009a;Hotta et al, 2009b). We used EOS-S(4+)-EmGFP reporter (Hotta et al, 2009b) manufactured as BacMam viruses ( Fig.…”
Section: Fully Reprogrammed Ips Cell Lines Generated By the Bacmam Trmentioning
confidence: 99%
“…Ecotropic gammaretrovirus has also been used more recently to deliver oncogenes to human cells; in the context of cellular reprogramming, the use of mSlc7a1 to avoid generation of amphotropic virus harboring human oncogenes is well established. 4,5 However, lentivirus provides significant advantages over gammaretrovirus in transducing refractory cell populations, 6 including primary cells that are often desirable targets for reprogramming, because the lentiviral pre-integration complex allows transduction of non-dividing cells. 7 Lentiviruses have been produced with dozens of different pseudotypes, including MLV, in an effort to alter virus tropism, toxicity, and other properties.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent improvements have been made by using lentiviral vectors to deliver SV40T, UTF1 or p53 shRNA to supplement the reprogramming cocktails, resulting in a 70-100 fold increase in reprogramming efficiency (Mali et al, 2008;Zhao et al, 2008). Moreover, reporter and antibiotic selection casettes have also been incorporated into lentiviral vectors to aid in the isolation of iPSC (Hotta et al, 2009a;Hotta et al, 2009b). Previous studies indicated that transient expression of reprogramming factors is sufficient to activate the endogenous pluripotent gene program to allow for direct cell reprogramming Takahashi and Yamanaka, 2006).…”
Section: Lentiviral Vectorsmentioning
confidence: 99%